Correlation analysis between agronomic character and yield of Padjadjaran maize hybrids at medium and high population densities - Yuwariah, Yuyun; Haysa, Qinthara Nail; Muhammad, Damara Bakti; Ruswandi, Dedi; Wicaksono, Fiky Yulianto (Kultivasi, 2023)
Maize is a prospective food commodity that developed in Indonesia. The use of hybrid corn gives better yield than open-pollinated varieties. Spacing management in hybrid maize production can reduce competition between plants, so that the plant canopy and roots can grow optimally. This research aimed to compare the differences in the phenotypic performance of the agronomic characters of Padjadjaran maize hybrid, determine the dominant agronomic characteristics, and determine the correlation between the growth and yield characteristics at medium- and high-population densities. The experiment was carried out from December 2021 until May 2022 at Sanggar Penelitian, Latihan dan Pengembangan Pertanian (SPLPP) Universitas Padjadjaran, Arjasari, Bandung Regency. This experiment used Randomized Completely Block Design analysis with 20 treatments of Padjadjaran maize hybrids and 4 check varieties, all treatments were replicated 3 times in both population densities. Statistical analysis used multiple regression linear analysis and correlation test. The experimental results showed that the yield of 20 genotypes of Padjadjaran maize hybrids at medium population density was influenced by the ear length, number of seeds per row, and number of seed rows, while in the high population density, it was influenced by number of seed rows. Correlation analysis revealed a positive and significant relationship between the growth and yield components in medium population density. Meanwhile, the correlation at high population density between the components of growth and yield was not consistent.